Análise de ambientação de aplicações PHP e .NET em nuvem: um estudo baseado em desempenho - Silva, Luiz Henrique Oliveira (2025)
Programming languages, in their general aspects, share the primary objective of solving computational problems, despite having distinct characteristics. Therefore, this study provides a comparative analysis between PHP, a dynamically-typed language interpreted at runtime, and C#, a .NET platform language which is strongly-typed and pre-compiled into intermediate code. Using two languages with fundamentally different operational modes is useful for understanding behaviors that can be generalized to other similar languages. The comparison is conducted within cloud environments, specifically AWS and Azure, selected based on performance, popularity, scalability, and developer adoption criteria. For load-testing these applications, the tools JMeter and K6 were selected after an initial analysis of leading open-source performance testing tools. Tests involving read and write operations were executed, enabling the identification of significant differences in behavior between the analyzed environments. AWS presented superior results for read operations, while Azure stood out in write operations, particularly with .NET applications. The findings also highlighted significant differences in operational costs between the evaluated environments. Thus, this study provides valuable insights to assist in the careful selection of cloud providers, considering performance, predominant application operations, and available budget.